Implementasi Asesmen Diagnostik dalam Pembelajaran IPAS Kurikulum Merdeka pada Aspek Penilaian Berpikir Kritis Siswa - Chotimah, Chotimah (Jurnal Didaktika Pendidikan Dasar, 2025)
The implementation of the Independent Curriculum emphasizes the importance of developing students’ critical thinking skills, but there are still teachers who do not understand and apply diagnostic assessments effectively in science learning to measure this ability. In addition, students' critical thinking assessments are often ignored in daily learning practices, so in-depth research is needed to evaluate and optimize the use of diagnostic assessments as a measuring tool that can facilitate the development of critical thinking skills in accordance with the demands of the Independent Curriculum. This study aims to determine the implementation of diagnostic assessments in science learning on the aspect of critical thinking assessments of students at SDN Banjar 4, Galis District. This research method uses a qualitative phenomenological design. Data collection techniques include interviews, observations, documentation and literature studies. The subjects in this study were 12 fourth grade students of SDN Banjar 4. The results of this study are cognitive diagnostic assessments carried out by teachers as follows: high group (top) 83.33%; middle group (middle) 16.67% and low group (bottom) 0%. Diagnostic assessments have a significant impact on the learning process and the development of students' critical thinking skills. Teachers can also understand students' initial understanding of the material to be taught and provide an initial picture of students' abilities.